Emergence of a NDM-1-producing ST25 Klebsiella pneumoniae strain causing neonatal sepsis in China - Zhao, Junhui; Zheng, Beiwen; Xu, Hao; Li, Junfeng; Sun, Tengfei; Jiang, Xiawei; Liu, Wenhong (Frontiers in Microbiology, 2022)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) seriously threaten the efficacy of modern medicine with a high associated mortality rate and unprecedented transmission rate. In this study, we isolated a clinical K. pneumoniae strain DY1928 harboring blaNDM-1 from a neonate with blood infection. Antimicrobial susceptibility testing indicated that DY1928 was resistant to various antimicrobial agents, including meropenem, imipenem, ceftriaxone, cefotaxime, ceftazidime, cefepime, piperacillin-tazobactam, and amoxicillin-clavulanate. S1 nuclease-pulsed field gel electrophoresis (S1-PFGE), southern blot and conjugation experiment revealed that the blaNDM-1 gene was located on a conjugative plasmid of IncA/C2 type with a 147.9 kb length. Whole-genome sequencing showed that there was a conservative structure sequence (blaNDM-1-ble-trpF-dsbD) located downstream of the blaNDM-1 gene. Multilocus sequence typing (MLST) classified DY1928 as ST25, which was a hypervirulent K. pneumoniae type. Phylogenetic analysis of genomic data from all ST25 K. pneumoniae strains available in the NCBI database suggested that all blaNDM-1 positive strains were isolated in China and had clinical origins. A mouse bloodstream infection model was constructed to test the virulence of DY1928, and 11 K. pneumoniae strains homologous to DY1928 were isolated from the feces of infected mice. Moreover, we found that DY1928 had a tendency to flow from the blood into the intestine in mice and caused multiple organ damage. To our knowledge, this is the first study to report an infection caused by blaNDM-1-positive ST25 K. pneumoniae in the neonatal unit. Our findings indicated that stricter surveillance and more effective actions were needed to reduce the risk of disseminating such K. pneumoniae strains in clinical settings, especially in neonatal wards.